2019
DOI: 10.2174/1573401314666180223135430
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Zygophyllum album L Monofloral Honey from El-Oued, Algeria

Abstract: Background: Honey is generally evaluated by physicochemical analysis of its constituents. The manipulation of honey and its possible adulteration is reflected in many of its physicochemical properties. Objective: In this study, samples of Zygophyllum album L honey produced in El-Oued, Algeria, were characterized based on their melissopalynology, physicochemical and antioxidant properties, also polyphenol content. Methods: The physicochemical parameters of honey, such as density, moisture content, pH, free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Some authors studied the characteristics of honey produced in Algeria and found differing results as to the pollen content [ 8 , 9 , 10 , 13 ], physicochemical attributes and pollen profile of samples from different areas [ 7 , 14 , 15 , 16 ], their botanical origin [ 9 , 11 , 17 , 18 , 19 ], antibacterial and antioxidant activity [ 20 ], or specific compounds such as sugars and phenolic or volatile compounds [ 21 , 22 ]. However, honey production in Algeria remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors studied the characteristics of honey produced in Algeria and found differing results as to the pollen content [ 8 , 9 , 10 , 13 ], physicochemical attributes and pollen profile of samples from different areas [ 7 , 14 , 15 , 16 ], their botanical origin [ 9 , 11 , 17 , 18 , 19 ], antibacterial and antioxidant activity [ 20 ], or specific compounds such as sugars and phenolic or volatile compounds [ 21 , 22 ]. However, honey production in Algeria remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…The total antioxidant capacity of the honey samples was determined using the phosphomolybdenum technique with minor modifications, as reported by Mesbahi et al [88]. In brief, 0.2 mL samples of honey were combined with a 2 mL reagent solution (0.6 M sulfuric acid, 28 mM sodium phosphate, and 4 mM ammonium molybdate).…”
Section: Determination Of Total Antioxidant Activitymentioning
confidence: 99%
“…Essential oil extracted from aerial parts of Cotula cinerea analyzed by GC-MS showed that (E)-citral, limoneneepoxidecis-, thymol methyl ether, carvacrol, trans-carveol,carvone and trans-piperitol were the considerable compounds [12].Likewise,[10] noted the presence of 3-carène, thujone, santolinatriene and camphor from the oil obtained from a specimen collected in Oued Souf area.The chiral flavanones analysis isolated from methanol extract of cotula cinerae aerial parts by TLC methods showed the presence of three compounds: Hesperidin , Hesperitin and Eriodoctyol[3].The evaluation of antioxidant activity of Tetraena alba (L.f.) extracts showed that acid ascorbic have a considerable antioxidant effect[6]. Two phenolic compounds; Gallic acid and ascorbic acid were extracted from Tetraena alba (L.f.) floral honey, had a significatively antioxidant activity[24] [21]. reported the identification of three metabolites from whole plant of Caroxylonimbricatum(Forssk.…”
mentioning
confidence: 99%